Connecting Green Economy goals with innovation policy in Ethiopia - Mamo, Girma; Stamm, Andreas (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
Ethiopia aims to achieve middle-income status by 2025. When following the conventional development path, high growth rates would result in a sharp increase in greenhouse gas emissions and unsustainable use of natural resources. To avoid such negative effects, Ethiopia committed to put its growth model on a more climate friendly and sustainable basis.